The Role of Mass Eccentricity on the Earthquake Induced Torsion in Buildings - K. Georgoussis, George; Mamou, Anna (International Journal of Engineering and Technology, 2018)
This paper investigates the effect of mass eccentricity on the earthquake induced torsion in buildings. An analytical solution is proposed, which identifies the location of a key structural element for which the torsional response of a structure is minimized for any height wise variation of the mass eccentricities. The accuracy of the analytical solution is then verified with parametric numerical modelling on 9-story buildings with height wise variations of the accidental eccentricities. The numerical modeling results show that the top rotations and base torques have an inverted peak, which indicates an optimum location of the key structural element, for which the torsional response of the structure is minimized. The location of the key element which minimizes the torsional response of the structure predicted by the analytical solution is verified with reasonable accuracy by the numerical modeling results.Â Â Â Â Â Â Â Â